Corporate Social Responsibility and Spirituality: Islamic Perspective - Rochayatun, Sulis; Andriyani, Fitriya (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2023)
Scientific concern regarding CSR continues to grow in the business world. Previously, CSR studies did not include elements of morally binding values. Then this phenomenon developed by entering spirituality as a source of important values in CSR. Therefore, the literature on the topic must provide an up-to-date overview of religion-based CSR research. This literature aims to understand the concept of CSR based on Islamic spirituality. This literature review has five main stages, namely identifying research questions, identifying relevant studies, study selection, making data charts, compile, summarize and report results. The studies reviewed were from the Emerald, Springer, and Taylor Francis electronic databases. The study results show that from an Islamic perspective, CSR leads to social justice, and CSR is completely selfless in creating prosperity. The implications of this study are expected to be a reference and guideline in implementing CSR based on Islamic spirituality which adheres to religious values with the aim of justice and social welfare, so that companies can achieve sustainability.